The Effectiveness of Inside-Outside Circle and Jigsaw Techniques in Teaching Interpersonal Conversation for High and Low Self-Confident Students - Carascalao, Oscar Yustino; Anggani Linggar Bharati, Dwi; Faridi, Abdurrachman (English Education Journal, 2019)
This study is an experimental research with a factorial design which aimed to find out effectiveness of inside-outside circle and jigsaw techniques in teaching interpersonal conversation for high and low self-confident students. The samples of the study were tenth graders of SMA Krista Mitra Semarang the 2018/2019 academic year. There were two classes, experimental class I and experimental class II which every class consisted of 20 students. Inside-outside Circle technique was used in the experimental class I, while Jigsaw technique was used in experimental class II. To answer research questions number one up to four, T-test was used. To answer research question number five and six, students’ mean scores in experimental class I and II were compared. While two-ways ANOVA with F-test at the 5% (0.05) level of significance was used to answer the seventh question. The result of this study showed that inside-outside circle and jigsaw techniques are effective to be used in teaching interpersonal conversation for high and low self-confident students. There were no significant differences of achievement between high and low self-confidence students using inside-outside circle and jigsaw techniques. For the interaction among the variables, it shows that there was no interaction among the techniques, students’ self-confidence, and students’ interpersonal conversation skill.